2017
DOI: 10.1051/0004-6361/201629775
|View full text |Cite
|
Sign up to set email alerts
|

Multiwavelength variability study and search for periodicity of PKS 1510–089

Abstract: Context. Blazars are the most luminous and variable active galactic nuclei (AGNs), and thus excellent probes of accretion and emission processes close to the central engine.Aims. We concentrate here on PKS 1510-089 (z = 0.36), a member of the Flat-Spectrum Radio Quasar variety of blazars, an extremely powerful gamma-ray source and one of the brightest in the Fermi LAT catalog, to study the complex variability of its bright multiwavelength spectrum, identify the physical parameters responsible for the variation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 194 publications
(192 reference statements)
2
28
0
Order By: Relevance
“…The peak observed at the edge of the DCF can be discarded. A time lag of 50 days between gamma-rays and X-rays has been seen by Castignani et al (2017) in PKS 1510-089. This time lag between gamma-rays and X-rays suggests that the X-rays might have been produced far away from the region of gamma-ray emission in the jet.…”
Section: Cross-correlationmentioning
confidence: 97%
“…The peak observed at the edge of the DCF can be discarded. A time lag of 50 days between gamma-rays and X-rays has been seen by Castignani et al (2017) in PKS 1510-089. This time lag between gamma-rays and X-rays suggests that the X-rays might have been produced far away from the region of gamma-ray emission in the jet.…”
Section: Cross-correlationmentioning
confidence: 97%
“…More recently, Sandrinelli et al (2016) were looking for QPOs in multiwavelength data of PKS 1510−089, uncovering a HE γ-ray periodicity with a period of 115 days at the 2.58σ significance level, and two optical peaks at 345 and 575 days. On the other hand, neither Castignani et al (2017) nor Gupta et al (2019) found any QPOs in 8-years-long and 7-years-long Fermi -LAT LCs, respectively.…”
Section: Txs 0506+056mentioning
confidence: 75%
“…Similar to other radio-loud AGNs, PKS 1510-089 shows strong flux variation across the entire electromagnetic spectrum from radio to γ ray (e.g., Malkan & Moore 1986;Tavecchio et al 2000;Bach et al 2007;Abdo et al 2010a;Marscher et al 2010;Orienti et al 2013;H.E.S.S. Collaboration 2013;Kushwaha et al 2016;Beaklini et al 2017;Castignani et al 2017;Prince et al 2019). However, the BLR of PKS 1510-089 remains poorly studied due to its strong radio emission, although the size of its BLR is an important model parameter in the multi-band SED fitting.…”
Section: Introductionmentioning
confidence: 73%
“…Using UV data, Abdo et al (2010a) estimated a black hole mass for PKS 1510-089 as M BH = 5.4 × 10 8 M . On the other hand, Castignani et al (2017), using the Shakura & Sunyaev (1973) model, estimated a black hole mass of 2.4 × 10 8 M . Therefore, a large range of black hole masses, 1−9 × 10 8 M , for PKS 1510-089 has been reported in the literature.…”
Section: Black Hole Mass Measurementmentioning
confidence: 99%